High pure substances for astrophysical research - Kovtun, G.P. (Вопросы атомной науки и техники, 2020)
The features of the application of high-purity substances for studying rare nuclear events in astrophysics, in particular double beta decay, are considered. It was noted that for such studies, the special underground laboratories are needed to eliminate the cosmic radiation background, and the use of high-purity materials for possibility to record rare nuclear events. The content of neutral impurity elements should not exceed 0.1 ppm, and the level of radionuclide contamination should be less than units mBq/kg. At the NSC KIPT, the technologies have been developed for the production of high-purity refractory (W, Mo, Re, Ru, Os) and low-melting metals (Zn, Cd, Te, archPb), including isotopically-enriched ¹⁰⁶Cd, ¹¹⁶Cd, satisfying these requirements. Using these metals both as individual elements and as part of low-background scintillation single crystals, it was possible to obtain a number of new fundamental results in the field of astrophysics, together with the Institute for Nuclear Research of the National Academy of Sciences of Ukraine and the Gran Sasso Laboratory of the National Institute of Physics (Italy).